Le numérique, support des potentialités du récit ? - Florence Rio; Elsa Tadier (Cahiers de Narratologie)
This article examines the potential of choice-based narratives in the construction of the reading practices of 12 to 15 year olds currently targeted by educational policies. In particular, it questions the role and effects of digital media in the reception of this type of narrative, which explicitly constructs the expectation of an "action" by this adolescent public. As a singular genre with characteristics in common with the so-called "interactive" narrative, the choice narrative allows us to reflect on the forms of adherence to the narrative itself or to the medium. The survey presented here highlights that the added value, the attraction and the motivation often attributed to the "innovative" character of digital devices is not self-evident: the reading practices of the young people surveyed show a much more nuanced relationship to digital as a medium for reading and engagement. It is therefore a question of pointing out the different roles that digital media can play (and sometimes alternately) as either adjuvants or hindrances in the relationship that young readers have with the narrative.